Professionalism and teachers' response to computers in the classroom - Bennie, Marc (School of Education, 2014)
During the last twenty years, there have been telling changes in how teachers teach and schools are run. One major reason for this has been the growth of Information and Communication Technologies (lCT). A consequence of the growth of these technologies has been a change in the global economy, which has become increasingly interconnected and dictated by profits. Teachers have had to adapt to this new global landscape. The changes required have not been easy. This study sought to find out more about the implication of these changes in teachers professional lives. The key findings point to a change in the work that teachers do as a result of computer technology and increased attention to market related practices in schools. Teachers have also had to explore different approaches to teaching and learning . These changes have thrust teacher's professional identities into the limelight as the profession adapts to the prevailing circumstances.